Living wages in Malaysia: the sustainability among Fresh Graduates in Klang Valley / Noor Fatin Fatiha Hamamilin and Aimeen Sarah Hanini Amir Husnizan - Hamamilin, Noor Fatin Fatiha; Amir Husnizan, Aimeen Sarah Hanini (2022)
In Malaysia, some of the fresh graduates living in the Klang Valley find it hard to sustain as the cost of living in the urban areas are high. In this paper, it studies on problem that are affecting the sustainability of fresh graduates based on the living wages. In Malaysia, there is only policy for setting the minimum wages however, there are no source of effort on uplifting the people’s quality of life especially the fresh graduates. Living wages and minimum wages are different as living wages are wages that are paid to the workers so that they can enjoy the minimum benefit. The living wages are not enough to satisfy the living cost of the fresh graduates in Klang Valley. The purpose of this study is to examine the living wages with the factors that would affect the sustainability among fresh graduates in Klang Valley. This paper used quantitative research by survey, and it was then distributed to many different platforms for fresh graduates in Klang Valley to answer. This paper shows that positive relationships between financial education, spending habits and family dependency with the sustainability of fresh graduates. It is expected for the government to take charge on taking care of the rights of the fresh graduates.